2020
DOI: 10.1093/jbcr/iraa154
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Burn Injuries in Northern Israel During the COVID-19 Lockdown

Abstract: Coronavirus disease 2019 obliged many countries to apply lockdown policies to contain the spread of infection. The restrictions in Israel included limitations on movement, reduction of working capacity and closure of the educational system. The present study focused on patients treated at a referral center for burns in northern Israel. Our goal was to investigate temporal variations in burn injuries during this period. Data was retrospectively extracted from the medical records of burn patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
2
26
5
Order By: Relevance
“…The major mechanism of burn injuries under stay-at-home orders or lockdowns is universally reported as flame burns [12] , [19] , [24] , and similar results were obtained in this study. The relatively higher incidence of injuries in a closed space and inhalation injuries is likely due to the prolonged stay of people at home.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The major mechanism of burn injuries under stay-at-home orders or lockdowns is universally reported as flame burns [12] , [19] , [24] , and similar results were obtained in this study. The relatively higher incidence of injuries in a closed space and inhalation injuries is likely due to the prolonged stay of people at home.…”
Section: Discussionsupporting
confidence: 89%
“…While various studies have reported the reduction of burn injuries under stay-at-home orders or during lockdown periods [11] , [12] , [23] , [24] , the number of patients during the stay-at-home order did not decrease in this study. This may be because Tokyo citizens were only asked, rather than mandated, to refrain from going outside.…”
Section: Discussioncontrasting
confidence: 75%
“…However, these centers also did not have any COVID-19-positive burns. 11,12 The drop in new admissions during the pandemic period can be attributed to lockdown restrictions and fear among patients from coming to hospitals. This has also led to patients landing late in the hospital after worsening of their condition, highlighting the need for stricter transfer guidelines for burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al 4 and Greenhalgh 5 described increased burn center admissions, while Kruchevsky described decreased admissions overall, but increased levels in the pediatric and female demographic categories. 3 Keays et al 6 showed a remarkable reduction in traumatic injuries presenting to Montreal Children’s Hospital, Canada.…”
Section: To the Editormentioning
confidence: 99%